2022
DOI: 10.3390/cancers14143367
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Cell-Free DNA Profiling Predicts the Therapeutic Outcome in Advanced Hepatocellular Carcinoma Patients Treated with Combination Immunotherapy

Abstract: Combination immunotherapy with anti-programmed cell death1-ligand1 (PD-L1) and anti-vascular endothelial growth factor (VEGF) antibodies has become the standard treatment for patients with unresectable HCC (u-HCC). However, limited patients obtain clinical benefits. Cell-free DNA (cfDNA) in peripheral blood contains circulating tumor DNA (ctDNA) that reflects molecular abnormalities in tumor tissue. We investigated the potential of cfDNA/ctDNA as biomarkers for predicting the therapeutic outcome in u-HCC patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…It has been previously reported that a high baseline cfDNA concentration is related to poor prognosis in tumors other than HCC [16, 25, 26]. Prior research has underscored the prognostic value of cfDNA in advanced HCC [27, 28]. However, these studies primarily focused on the genetic profiling of cfDNA.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that a high baseline cfDNA concentration is related to poor prognosis in tumors other than HCC [16, 25, 26]. Prior research has underscored the prognostic value of cfDNA in advanced HCC [27, 28]. However, these studies primarily focused on the genetic profiling of cfDNA.…”
Section: Discussionmentioning
confidence: 99%
“…High pre-treatment cfDNA levels were associated with a lower response rate and shorter PFS and OS. Further, the presence of a TERT mutation and a serum AFP levels ≥400 ng/mL were independent predictors of poor OS after treatment with atezolizumab combined with bevacizumab [173].…”
Section: Circulating Tumor Dna and Circulating Tumor Cellsmentioning
confidence: 91%
“…CfDNA in peripheral blood contains circulating tumor DNA (ctDNA) that reflects molecular abnormalities in tumor tissue. The potential of cfDNA/ctDNA can be investigated as biomarkers for predicting the therapeutic outcome in unresectable hepatocellular carcinoma (u-HCC) patients treated with anti-PD-L1/VEGF therapy ( Matsumae et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%